Unexpected role of metal halides in a chalcogenide glass network. (April 2022) - Zaiter, Rayan; Kassem, Mohammad; Fontanari, Daniele; Sokolov, Anton; Usuki, Takeshi; Bokova, Maria; Hannon, Alex C.; Benmore, Chris J.; Cousin, Fabrice; Ozheredov, Ilya; Bychkov, Eugene
Graphical abstract: Highlights: Silver halides in AgY-As2 S3 (Y = Br, I) glasses behave as unconventional modifiers. Formation of terminal sulfur with AgY additions is accompanied by increasing fraction of As-As homopolar bonds for 16% of arsenic species. AgY monomers are distributed randomly in AgY-poor glasses (≲ 2–3 at.% Ag) Edge- and corner-sharing Ag[Br2 S2 ] tetrahedra are forming preferential conduction pathways in AgBr-rich glasses (≳ 10 at.% Ag) Abstract: Chalcogenide glasses containing light alkali and Group 11 (Cu, Ag) halides MY (Y = Cl, Br, I) exhibit high ionic conductivity while their heavy alkali counterparts show promising properties for optical applications. The structural role of metal halides in chalcogenide glass networks remains either essentially unknown (alkali halides) or controversial (CuY, AgY). In addition, possible structural changes as a function of MY content have not been reported. Using pulsed neutron diffraction, high-energy X-ray scattering, Raman spectroscopy and FPMD modeling, we show unexpected role of silver halides as unconventional modifiers taking two contrasting glass compositions: (AgI)0.1 (As2 S3 )0.9 (critical percolation domain) and (AgBr)0.5 (As2 S3 )0.5 (modifier-controlled region) as an example. The latter alloy seems to be a promising precursor for thermoelectric applications. The deep insight into the glass structure on the short- and intermediate-range scale, including an enhanced chemical disorder, enables a rational design of these functional materials.